Interdependency and Cascading Failures in Co-Patenting and Shareholding Interfirm Networks - Daniel Marcolin; Yasuyuki Todo; Mahendra Piraveenan (IEEE Access)
This work analyses the interdependent link creation of patent and shareholding links in interfirm networks, and how this dynamics affects the resilience of such networks in the face of cascading failures. Using the Orbis dataset, we construct very large co-patenting and shareholding networks, globally as well as in terms of individual countries. Besides, we construct smaller overlap networks from those firm pairs which have both types of links between them, for nine years between 2008-2016. We use information theoretic measures, such as mutual information, active information storage, and transfer entropy, to characterise the topological similarities and shared topological information between the relevant co-patenting and shareholding networks. We then construct a cascading failure model, and use it to analyse the resilience of interdependent interfirm networks in terms of multiple failure characteristics. We find that there is relatively high level of mutual information between co-patenting networks and the shareholding networks from later years, suggesting that the formation of shareholding links is influenced by the existence of patent links in previous years. We highlight that this phenomena differs between countries. For interfirm networks from certain countries, such as Switzerland and Netherlands, this influence is remarkably higher compared to other countries. We also show that this influence becomes most apparent after a delay of four years between the formation of co-patenting links and shareholding links. Analysing the resilience of shareholding networks against cascading failures, we show that in terms of both mean downtime, and failure proportion of firms, certain countries including Italy, Germany, India, Japan and the United States, have less resilient shareholding networks compared to other countries with significant economies. Based on our results, we postulate that an interfirm network model which considers multiple types of relationships together, uses information theoretic measures to establish information sharing and causality between them, and uses cascading failure simulation to understand the resilience of such networks under economic and financial stress, could be a useful multifaceted model to highlight important features of economic systems around the world.